A method for increasing specific surface area and needle punching adaptation modification of pan-based pre-oxidized filaments for thin electrodes of liquid flow batteries

CN122980197APending Publication Date: 2026-10-27ZHEJIANG BAOJING CARBON MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610889475.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]第一,原生比表面积偏低,内部开孔比例有限,表面光滑惰性位点多,无法为钒系、铁铬系等液流电池电化学反应提供充足活性位点,电解液浸润性差、离子传质阻力大,制成薄电极后极化损耗明显,制约电池能量效率提升;

Benefits of technology

[0022](1)本发明以常规PAN基预氧丝为起始原料,无需特殊前置改性,仅通过50–200nm浅表层精准刻蚀,靶向去除表面硬脆约束层与松散结构,不破坏纤维内部骨架与分子取向,从根源上同步解决预氧丝比表面积不足和针刺成型易断纤两大痛点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980197A_ABST
    Figure CN122980197A_ABST
Patent Text Reader

Abstract

The application discloses a PAN-based pre-oxidized yarn specific surface area and needle punching adaptive modification method for thin electrode of a liquid flow battery, relates to the technical field of carbon fiber precursor functional modification and key materials of a liquid flow battery, and uses conventional PAN-based pre-oxidized yarn as raw material, adopts low-temperature plasma for controllable shallow layer uniform etching, removes the hard and brittle constraint layer and loose surface layer structure of the fiber surface in a targeted manner, and does not damage the internal skeleton and molecular orientation structure of the fiber.The breaking strength of the application decreases slightly, the strength retention rate reaches more than 95%, the specific surface area of the pre-oxidized yarn is significantly improved to 3.0-6.0 m2 / g, the elongation at break is improved from 16%-18% to 22%-24%, the fiber flexibility, bending resistance and fiber adhesion are greatly improved, and the double technical problems of insufficient specific surface area of ordinary pre-oxidized yarn and poor needle punching forming of thin carbon felt are solved simultaneously from the source of the precursor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional modification of carbon fiber precursors and key materials for flow batteries. Specifically, it relates to a method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized filaments for thin electrodes in flow batteries. This method is applicable to the precursor modification of needle-punched carbon felt for thin electrodes in flow batteries, and can simultaneously improve the specific surface area and needle-punching performance of pre-oxidized filaments, thereby optimizing the electrochemical performance and preparation yield of flow battery electrodes. Background Technology

[0002] As one of the mainstream technologies in the field of large-scale, long-term energy storage, flow batteries possess outstanding advantages such as independent power capacity design, long cycle life, safety and flame retardancy, and strong environmental adaptability. They have significant application value in new energy consumption, grid peak shaving, industrial park energy storage, and microgrid systems. Electrodes are the core functional carriers for electrochemical reactions, electrolyte penetration, and ion conduction in flow batteries. Their microporous structure, specific surface area, surface activity, and matrix mechanical stability directly determine the degree of battery polarization, energy efficiency, and long-term cycle stability.

[0003] As energy storage systems evolve towards lighter weight, thinner layers, and higher power density, traditional thick-layer carbon felt electrodes suffer from drawbacks such as long ion diffusion paths, large concentration polarization, slow response rates, and high volumetric weight. Thin-layer carbon felt electrodes have become an inevitable trend in the industry. Thin electrodes require substrates with high specific surface area, a reasonable pore structure, excellent flexibility, and adaptability to needle punching, placing far more stringent demands on the structure and mechanical properties of the precursor raw materials than on ordinary carbon felt.

[0004] Currently, PAN-based pre-oxidized fibers are commonly used as precursors in the industrial fabrication of carbon felt electrodes for flow batteries. However, existing conventional PAN-based pre-oxidized fibers have inherent structural defects:

[0005] First, the original specific surface area is relatively low, the proportion of internal openings is limited, and the surface is smooth with many inert sites, which cannot provide sufficient active sites for the electrochemical reactions of vanadium-based, iron-chromium-based and other flow batteries. The electrolyte wettability is poor and the ion mass transfer resistance is large. After the thin electrode is made, the polarization loss is obvious, which restricts the improvement of battery energy efficiency.

[0006] Secondly, during the pre-oxidation process, the fibers spontaneously form a dense, hard, and brittle outer layer. This layer has a high degree of cyclization, high brittleness, and poor deformation coordination, resulting in the raw material's elongation at break being concentrated in the range of 16% to 18%, indicating insufficient flexibility. Under the high-speed needle punching process of ultra-thin carbon felt, the fibers are prone to stress concentration, splitting, and breakage, leading to forming defects such as fiber breakage, web breakage, localized wrinkling, poor felt surface flatness, and large areal density dispersion. This not only reduces the product yield but also causes uneven local current distribution in thin electrodes and accelerated long-term cycle decay.

[0007] Third, the existing improvement routes in the industry have obvious shortcomings: the mainstream approach is to use acid and alkali / high temperature etching after finishing the carbon felt to increase the specific surface area. Although this can slightly increase the specific surface area, it will indiscriminately erode the fiber skeleton, destroy the carbon felt interwoven structure, and significantly reduce the mechanical strength. Under thin electrode conditions, it is easy to deform, delaminate, and shed powder. Other methods such as chemical impregnation and grafting modification are used to improve surface properties, but reagent residues can easily introduce impurities and contaminate the electrolyte. Moreover, most of these are overall modifications, which cannot achieve targeted control of only the surface layer. This can easily damage the mechanical properties of the fiber and make it difficult to simultaneously achieve the three major indicators of high specific surface area, high strength retention rate, and needle punching flexibility.

[0008] In summary, existing conventional PAN-based pre-oxidized fibers are ill-suited to the comprehensive requirements of high specific surface area, high flexibility, high molding yield, and high mechanical stability for thin electrodes in flow batteries. Furthermore, post-processing modification and traditional chemical modification both suffer from structural damage, impurity residues, and an inability to achieve a synergistic performance balance. Therefore, developing a PAN-based pre-oxidized fiber modification method that employs a gentle process, precise surface etching without damaging the internal fiber skeleton, and simultaneously improves specific surface area, elongation at break, and strength retention, thereby addressing the performance limitations and needle-punching challenges of carbon felt raw materials for thin electrodes at the precursor level, is a critical technological need urgently requiring breakthroughs in this field. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention aims to provide a method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized fibers for thin electrodes in flow batteries. By ensuring that the internal skeleton of the fiber is not damaged and the high strength is retained, the specific surface area is increased and the needle-punching flexibility is improved simultaneously. This method is adapted to the needs of needle-punched carbon felt preparation for thin electrodes in flow batteries, and solves the defects of existing conventional PAN-based pre-oxidized fibers, such as low specific surface area, insufficient elongation at break, easy fiber breakage during needle punching, and easy damage to the matrix structure and significant loss of mechanical properties after etching of carbon felt.

[0010] To achieve the above objectives, the present invention provides the following technical solution:

[0011] A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized filaments for thin electrodes in flow batteries is disclosed. The method uses PAN-based pre-oxidized filaments as raw materials for surface modification treatment. The method is characterized by using low-temperature plasma to perform targeted and controllable shallow etching treatment on the surface of PAN-based pre-oxidized fibers. The etching depth is controlled at 50–200 nm to target and remove the hard and brittle constraint layer and loose surface structure on the fiber surface without destroying the internal skeleton and molecular orientation structure of the fiber.

[0012] Furthermore, the low-temperature plasma is either air plasma or oxygen plasma. Through uniform plasma bombardment, it achieves gentle etching of the fiber surface, increasing the specific surface area of ​​conventional PAN-based pre-oxidized fibers to 3.0–6.0 m² / g. The breaking strength decreases slightly while retaining over 95% of its strength, and the breaking elongation increases from 16%–18% to 22%–24%. Fiber flexibility, bending resistance, and cohesion are significantly improved. While increasing the specific surface area to meet electrochemical requirements, it effectively reduces defects such as fiber breakage, web fragmentation, wrinkling, edge curling, and uneven surface density in thin needle-punched carbon felts.

[0013] Furthermore, the processing power of the low-temperature plasma is 50W–200W, and the processing time per batch is 30s–180s. The surface is gently etched by uniform plasma bombardment, without local over-etching or microcracks. Only the hard and brittle constraint layer and loose structure on the surface are removed, without damaging the internal mechanical skeleton of the fiber.

[0014] Furthermore, the PAN-based pre-oxidized filament has a fiber diameter of 9μm–14μm, an oxygen index greater than 42%, a heat shrinkage rate of no more than 2.0%, and a loose, interconnected pore structure inside the fiber.

[0015] Furthermore, the fracture strength retention rate of the etched and modified pre-oxidized filament is not less than 95%, and the mechanical properties of the fiber meet the requirements for needle punching and subsequent use as a thin electrode.

[0016] Furthermore, the elongation at break of the etched and modified pre-oxidized filament is 22%–24%, and the specific surface area is 3.0 m² / g–6.0 m² / g.

[0017] Furthermore, the fracture strength of the etched and modified pre-oxidized filament is not less than 2.4 cN / dtex.

[0018] Furthermore, after etching and modification, uniform nanogrooves and active sites are formed on the surface of the pre-oxidized fiber, which increases the specific surface area of ​​conventional PAN-based pre-oxidized fiber while enhancing electrolyte wettability and ion transport efficiency.

[0019] Furthermore, the obtained modified pre-oxidized filaments were used to prepare needled carbon felt for thin electrodes in flow batteries.

[0020] A high specific surface area needle-punched adaptable PAN-based pre-oxidized filament is prepared by the modification method according to any one of claims 1 to 8; the pre-oxidized filament has a specific surface area of ​​3.0 m² / g–6.0 m² / g, a breaking strength of not less than 2.4 cN / dtex, a breaking elongation of 22%–24%, and has a uniform surface, good flexibility, and strong cohesion.

[0021] Compared with the prior art, the beneficial effects of the present invention are:

[0022] (1) This invention uses conventional PAN-based pre-oxidized yarn as the starting material. No special pre-modification is required. It only uses 50–200nm shallow surface layer to precisely etch and remove the hard and brittle constraint layer and loose structure on the surface without damaging the internal skeleton and molecular orientation of the fiber. It solves the two major problems of insufficient specific surface area of ​​pre-oxidized yarn and easy fiber breakage during needle punching at the root.

[0023] (2) The specific surface area of ​​the modified product is increased to 3.0–6.0 m² / g, which can provide sufficient electrochemical active sites, improve electrolyte wettability and ion conduction ability; the elongation at break is increased from 16%–18% to 22%–24%, the fiber flexibility and bending resistance are significantly improved, the defects such as needle-punched fiber breakage, web breaking and wrinkling of thin carbon felt are greatly reduced, and the product molding yield is improved.

[0024] (3) The modified fracture strength retention rate of this invention can reach more than 95%, with minimal loss of overall mechanical properties. The modified fracture strength is not less than 2.4 cN / dtex, taking into account high specific surface area, high flexibility and high mechanical stability, and fully adapting to the long-term working conditions of thin electrodes in flow batteries.

[0025] (4) The present invention uses low-temperature plasma surface modification, which is a mild process with no chemical agents involved and no residual pollution. The parameters are controllable and suitable for continuous industrial production. Compared with traditional acid and alkali etching and high-temperature post-treatment, it has less structural damage, higher yield, and wider applicability. Attached Figure Description

[0026] Figure 1 This is a process flow diagram of a method for increasing the specific surface area of ​​PAN-based pre-oxidized filaments and for needle-punching adaptation modification for thin electrodes in flow batteries according to the present invention. Detailed Implementation

[0027] The technical solutions of the present invention will now be described in detail with reference to the accompanying drawings.

[0028] A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized filaments for thin electrodes in flow batteries, using PAN-based pre-oxidized filaments as raw materials for surface modification treatment, is characterized by using low-temperature plasma to perform targeted and controllable shallow layer etching treatment on the fiber surface, with the etching depth controlled at 50–200 nm, to target and remove the hard and brittle constraint layer and loose surface structure on the fiber surface without destroying the internal skeleton and molecular orientation structure of the fiber.

[0029] Furthermore, the low-temperature plasma is either air plasma or oxygen plasma. Through uniform plasma bombardment, it achieves gentle etching of the fiber surface, increasing the specific surface area of ​​conventional PAN-based pre-oxidized fibers to 3.0–6.0 m² / g. The breaking strength decreases slightly while retaining over 95% of its strength, and the breaking elongation increases from 16%–18% to 22%–24%. Fiber flexibility, bending resistance, and cohesion are significantly improved. While increasing the specific surface area to meet electrochemical requirements, it effectively reduces defects such as fiber breakage, web fragmentation, wrinkling, edge curling, and uneven surface density in thin needle-punched carbon felts.

[0030] Furthermore, the processing power of the low-temperature plasma is 50W–200W, and the processing time per batch is 30s–180s. The surface is gently etched by uniform plasma bombardment, without local over-etching or microcracks. Only the hard and brittle constraint layer and loose structure on the surface are removed, without damaging the internal mechanical skeleton of the fiber.

[0031] Furthermore, the PAN-based pre-oxidized filament has a fiber diameter of 9μm–14μm, an oxygen index greater than 42%, a heat shrinkage rate of no more than 2.0%, and a loose, interconnected pore structure inside the fiber.

[0032] Furthermore, the fracture strength retention rate of the etched and modified pre-oxidized filament is not less than 95%, and the mechanical properties of the fiber meet the requirements for needle punching and subsequent use as a thin electrode.

[0033] Furthermore, the elongation at break of the etched and modified pre-oxidized filament is 22%–24%, and the specific surface area is 3.0 m² / g–6.0 m² / g.

[0034] Furthermore, the fracture strength of the etched and modified pre-oxidized filament is not less than 2.4 cN / dtex.

[0035] Furthermore, after etching and modification, uniform nanogrooves and active sites are formed on the surface of the pre-oxidized fiber, which increases the specific surface area of ​​conventional PAN-based pre-oxidized fiber while enhancing electrolyte wettability and ion transport efficiency.

[0036] Furthermore, the obtained modified pre-oxidized filaments were used to prepare needled carbon felt for thin electrodes in flow batteries.

[0037] A method for improving the specific surface area and needle-punching adaptation of PAN-based pre-oxidized filaments for thin electrodes in flow batteries, prepared by any one of the modification methods in claims 1 to 8; the pre-oxidized filaments have a specific surface area of ​​3.0 m² / g–6.0 m² / g, a tensile strength of not less than 2.4 cN / dtex, a tensile elongation of 22%–24%, and a uniform surface, good flexibility, and strong cohesion.

[0038] All embodiments and comparative examples of this invention use conventional PAN-based pre-oxidized yarn of the same specification as raw material: diameter 12μm, oxygen index 44%, heat shrinkage rate 1.6%, specific surface area 1.8m² / g, tensile strength 2.6cN / dtex, and elongation at break 17.0%.

[0039] like Figure 1 As shown:

[0040] Example 1:

[0041] A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized fibers for thin electrodes in flow batteries includes the following steps:

[0042] Using the aforementioned conventional PAN-based pre-oxidized filament as raw material, the pre-oxidized filament was placed in a low-temperature plasma device with air plasma, a processing power of 50W, a processing time of 180s, and an etching depth controlled at 50nm to complete controllable shallow surface etching and obtain the modified pre-oxidized filament.

[0043] Modified pre-oxidized fibers were processed by carding, web laying, and needle punching to obtain 0.8mm pre-oxidized thin felt. Fiber breakage, web breaking, wrinkling, and edge curling were observed to evaluate the uniformity of the felt and the forming yield.

[0044] The pre-oxidized thin felt was carbonized, graphitized, and activated to obtain a thin electrode for the flow battery. The electrode was then assembled into the flow battery, and its energy efficiency and cycle stability were tested at a current density of 160 mA / cm².

[0045] Performance test results: specific surface area 3.2m² / g, tensile strength 2.56cN / dtex, strength retention 98.5%, elongation at break 22.0%; needle punching without mesh breakage or wrinkling, few broken fibers, and uniform felt surface density; battery energy efficiency 82.0%, capacity retention 85.0% (after 1000 cycles).

[0046] Example 2:

[0047] A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized fibers for thin electrodes in flow batteries includes the following steps:

[0048] (1) Using the above-mentioned conventional PAN-based pre-oxidized wire as raw material, the pre-oxidized wire is placed in a low-temperature plasma device, oxygen plasma is used, the processing power is 80W, the processing time is 120s, the etching depth is controlled to 80nm, and controllable shallow surface etching is completed to obtain modified pre-oxidized wire.

[0049] (2) The modified pre-oxidized fibers were processed by combing, web laying, needle punching and other treatments to obtain 0.8mm pre-oxidized thin felt. The fiber breakage, web breakage, wrinkling and edge curling were observed to evaluate the uniformity of the felt and the forming yield.

[0050] (3) The pre-oxidized thin felt was carbonized, graphitized and activated to obtain the thin electrode of the flow battery, which was then assembled into the flow battery. The energy efficiency and cycle stability were tested at a current density of 160 mA / cm².

[0051] Performance test results: specific surface area 3.9 m² / g, tensile strength 2.53 cN / dtex, strength retention rate 97.3%, elongation at break 22.7%; needle punching with no broken mesh or wrinkles, very few broken fibers, and uniform surface density of the felt; battery energy efficiency 82.6%, capacity retention rate 84.3% (after 1000 cycles).

[0052] Example 3:

[0053] A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized fibers for thin electrodes in flow batteries includes the following steps:

[0054] (1) Using the above-mentioned conventional PAN-based pre-oxidized wire as raw material, the pre-oxidized wire is placed in a low-temperature plasma device, using air plasma, with a processing power of 120W, a processing time of 90s, and an etching depth controlled at 120nm to complete controllable shallow surface etching and obtain modified pre-oxidized wire.

[0055] (2) The modified pre-oxidized fibers were processed by combing, web laying, needle punching and other treatments to obtain 0.8mm pre-oxidized thin felt. The fiber breakage, web breakage, wrinkling and edge curling were observed to evaluate the uniformity of the felt and the forming yield.

[0056] (3) The pre-oxidized thin felt was carbonized, graphitized and activated to obtain the thin electrode of the flow battery, which was then assembled into the flow battery. The energy efficiency and cycle stability were tested at a current density of 160 mA / cm².

[0057] Performance test results: specific surface area 4.6m² / g, tensile strength 2.51cN / dtex, strength retention 96.5%, elongation at break 23.1%; needle punching process with no fiber breakage, no web breakage, no wrinkling, and excellent felt flatness; battery energy efficiency 83.2%, capacity retention 84.1% (after 1000 cycles).

[0058] Example 4:

[0059] A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized fibers for thin electrodes in flow batteries includes the following steps:

[0060] (1) Using the above-mentioned conventional PAN-based pre-oxidized wire as raw material, the pre-oxidized wire is placed in a low-temperature plasma device, oxygen plasma is used, the processing power is 160W, the processing time is 70s, the etching depth is controlled to 160nm, and controllable shallow surface etching is completed to obtain modified pre-oxidized wire.

[0061] (2) The modified pre-oxidized fibers were processed by combing, web laying, needle punching and other treatments to obtain 0.8mm pre-oxidized thin felt. The fiber breakage, web breakage, wrinkling and edge curling were observed to evaluate the uniformity of the felt and the forming yield.

[0062] (3) The pre-oxidized thin felt was carbonized, graphitized and activated to obtain the thin electrode of the flow battery, which was then assembled into the flow battery. The energy efficiency and cycle stability were tested at a current density of 160 mA / cm².

[0063] Performance test results: specific surface area 5.3 m² / g, tensile strength 2.48 cN / dtex, strength retention 95.4%, elongation at break 23.4%; excellent needle punching, uniform and stable felt body; battery energy efficiency 83.9%, capacity retention 83.8% (after 1000 cycles).

[0064] Example 5:

[0065] A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized fibers for thin electrodes in flow batteries includes the following steps:

[0066] (1) Using the above-mentioned conventional PAN-based pre-oxidized wire as raw material, the pre-oxidized wire is placed in a low-temperature plasma device, using air plasma, with a processing power of 200W, a processing time of 45s, and an etching depth controlled at 200nm to complete controllable shallow surface etching and obtain modified pre-oxidized wire.

[0067] (2) The modified pre-oxidized fibers were processed by combing, web laying, needle punching and other treatments to obtain 0.8mm pre-oxidized thin felt. The fiber breakage, web breakage, wrinkling and edge curling were observed to evaluate the uniformity of the felt and the forming yield.

[0068] (3) The pre-oxidized thin felt was carbonized, graphitized and activated to obtain the thin electrode of the flow battery, which was then assembled into the flow battery. The energy efficiency and cycle stability were tested at a current density of 160 mA / cm².

[0069] Performance test results: specific surface area 5.7 m² / g, tensile strength 2.47 cN / dtex, strength retention 95.0%, elongation at break 23.8%; good needle punching with no obvious defects; battery energy efficiency 84.2%, capacity retention 83.7% (after 1000 cycles).

[0070] Comparative Example 1:

[0071] Compared to Example 1, no plasma etching was performed, but all other process conditions remained the same.

[0072] Performance test results: specific surface area 1.8m² / g, tensile strength 2.60cN / dtex, strength retention 100%, elongation at break 17.0%; severe fiber breakage, easy mesh breakage, easy wrinkling during needle punching, and low molding yield; battery energy efficiency 75.0%, capacity retention 76.3% (after 1000 cycles).

[0073] Comparative Example 2:

[0074] Compared with Example 1, no plasma etching was performed. Instead, the carbon felt electrode was post-etched using a conventional acid-base mixture to increase its specific surface area. All other process conditions remained the same.

[0075] Performance test results: The specific surface area of ​​the carbon felt was improved after etching, but the fiber body was significantly eroded by etching, resulting in a decrease in mechanical strength, easy shedding of powder, loose structure, and poor stability. The battery energy efficiency was 79.5%, and the capacity retention rate was 80.1% (after 1000 cycles). The overall performance was far lower than that of the embodiments of this invention.

[0076] The preferred embodiments of the present invention have been described in detail above with reference to the accompanying drawings. These embodiments are merely descriptions of preferred embodiments and are not intended to limit the scope or concept of the invention. The specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. Such combinations, as long as they do not violate the spirit of the present invention, should also be considered as part of this disclosure. To avoid unnecessary repetition, the present invention will not further describe the various possible combinations.

[0077] This invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this invention and without departing from the design idea of ​​this invention, all modifications and improvements made by those skilled in the art to the technical solutions of this invention should fall within the protection scope of this invention. The technical content for which protection is sought in this invention has been fully described in the claims.

Claims

1. A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized wires for thin electrodes in flow batteries, characterized in that PAN-based pre-oxidized wires are used as raw materials for surface modification treatment, and the method comprises: Low-temperature plasma is used to perform targeted and controllable shallow etching on the fiber surface, with the etching depth controlled at 50–200 nm, to target and remove the hard and brittle constraint layer and loose surface structure on the fiber surface.

2. The method for increasing the specific surface area of ​​PAN-based pre-oxidized wire and the needle-punching adaptation modification for thin electrodes in flow batteries according to claim 1, characterized in that, The low-temperature plasma is either air plasma or oxygen plasma, and the fiber surface is gently etched by uniform plasma bombardment.

3. A method for increasing the specific surface area and needle-punching adaptation of PAN-based pre-oxidized wires for thin electrodes in flow batteries according to any one of claims 1 or 2, characterized in that, The processing power of the low-temperature plasma is 50W–200W, and the processing time for a single batch is 30s–180s.

4. The method for increasing the specific surface area of ​​PAN-based pre-oxidized wire and the needle-punching adaptation modification for thin electrodes in flow batteries according to claim 1, characterized in that, The PAN-based pre-oxidized filament has a fiber diameter of 9μm–14μm, an oxygen index greater than 42%, a heat shrinkage rate of no more than 2.0%, and a loose, interconnected pore structure inside the fiber.

5. The method for increasing the specific surface area of ​​PAN-based pre-oxidized wire and the needle-punching adaptation modification for thin electrodes in flow batteries according to claim 1, characterized in that, The fracture strength retention rate of the etched and modified pre-oxidized filament is not less than 95%.

6. The method for increasing the specific surface area of ​​PAN-based pre-oxidized wire and the needle-punching adaptation modification for thin electrodes in flow batteries according to claim 1, characterized in that, The etched and modified pre-oxidized filament has an elongation at break of 22%–24% and a specific surface area of ​​3.0 m² / g–6.0 m² / g.

7. The method for increasing the specific surface area of ​​PAN-based pre-oxidized wire and the needle-punching adaptation modification for thin electrodes in flow batteries according to claim 1, characterized in that, The fracture strength of the etched and modified pre-oxidized filament is not less than 2.4 cN / dtex.

8. The method for increasing the specific surface area of ​​PAN-based pre-oxidized wire and the needle-punching adaptation modification for thin electrodes in flow batteries according to claim 1, characterized in that, After etching modification, uniform nanogrooves and active sites are formed on the surface of the pre-oxidized fiber, which increases the specific surface area of ​​conventional PAN-based pre-oxidized fiber while enhancing electrolyte wettability and ion transport efficiency.

9. The method for increasing the specific surface area of ​​PAN-based pre-oxidized wire and the needle-punching adaptation modification for thin electrodes in flow batteries according to claim 1, characterized in that, The resulting modified pre-oxidized filaments were used to prepare needled carbon felt for thin electrodes in flow batteries.

10. A high specific surface area needle-punched adaptable PAN-based pre-oxidized fiber, prepared by the modification method according to any one of claims 1 to 8, characterized in that, The pre-oxidized fiber has a specific surface area of ​​3.0 m² / g–6.0 m² / g, a tensile strength of not less than 2.4 cN / dtex, and a tensile elongation of 22%–24%.